Medical Cannabis and Industrial Hemp Tissue Culture: Present Status and Future Potential - Adhikary, Dinesh; Kulkarni, Manoj; El-Mezawy, Aliaa; Mobini, Saied; Elhiti, Mohamed; Gjuric, Rale; Ray, Anamika; Polowick, Patricia; Slaski, Jan J.; Jones, Maxwell P.; Bhowmik, Pankaj (Frontiers in Plant Science, 2021)
In recent years high-THC (psychoactive) and low-THC (industrial hemp) type cannabis (Cannabis sativa L.) have gained immense attention in medical, food, and a plethora of other consumer product markets. Among the planting materials used for cultivation, tissue culture clones provide various advantages such as economies of scale, production of disease-free and true-to-type plants for reducing the risk of GMP-EuGMP level medical cannabis production, as well as the development and application of various technologies for genetic improvement. Various tissue culture methods have the potential application with cannabis for research, breeding, and novel trait development, as well as commercial mass propagation. Although tissue culture techniques for plant regeneration and micropropagation have been reported for different cannabis genotypes and explant sources, there are significant variations in the response of cultures and the morphogenic pathway. Methods for many high-yielding elite strains are still rudimentary, and protocols are not established. With a recent focus on sequencing and genomics in cannabis, genetic transformation systems are applied to medical cannabis and hemp for functional gene annotation via traditional and transient transformation methods to create novel phenotypes by gene expression modulation and to validate gene function. This review presents the current status of research focusing on different aspects of tissue culture, including micropropagation, transformation, and the regeneration of medicinal cannabis and industrial hemp transformants. Potential future tissue culture research strategies helping elite cannabis breeding and propagation are also presented.